Quality of Life of Breast Cancer Patients Undergoing Chemotherapy at Hasan Sadikin Hospital Bandung - Lukmana Lokarjana; Sri Quintina Indriyana; Shena Solaiha Ismara; Fitriardi Sejati; Sri Yulia Rahayu (Jurnal EduHealth, 2026)
Breast cancer, the most common type of cancer diagnosed in women, is characterised by the growth of abnormal cells in the breast tissue. Chemotherapy is one of the main treatment methods for breast cancer, aimed at destroying cancer cells. Although effective, chemotherapy may cause various side effects that affect patients' quality of life. This study aimed to determine the quality of life of breast cancer patients undergoing chemotherapy at Hasan Sadikin Hospital Bandung. The study design was descriptive observational of breast cancer patients undergoing chemotherapy. The sample consisted of 35 individuals who met the inclusion criteria, selected using a consecutive technique. The instrument for measuring quality of life used the standard EORTC QLQC-C30, which measures global health status, functional scales, and symptom scales. The research results show that the quality of life of breast cancer patients undergoing chemotherapy has a global health status in the good category (73.8), functional scale in the good category (78.2), and symptom scale in the low category (28.6). The average quality of life of the patients is in the moderate category with a score of 685.8. Discussion, although global health status and functional scale are considered good, symptoms such as insomnia, vomiting, and decreased appetite remain a challenge. Ini mempengaruhi aktivitas sehari-hari dan hubungan sosial, yang dapat memperburuk ketidakseimbangan emosional dan psikologis pasien.